Prevalence and trends of vitamin D deficiency in a Saudi Arabian population: a five-years retrospective study from 2017 to 2021 - Madkhali, Yahya; Janakiraman, Balamurugan; Alsubaie, Faisal; Albalawi, Olayan; Alrashidy, Saleh; Alturki, Mohamad; Ahmed, Mehrunnisha; Manzar, Md Dilshad; Kashoo, Faizan (Frontiers in Public Health, 2025)
Vitamin D [25(OH)D] deficiency poses a significant global health concern, especially prevalent in developing nations. This retrospective cross-sectional study, conducted at King Khaled Hospital in Majmaah, aimed to investigate the prevalence and trends of vitamin D deficiency among 22,335 individuals from the Saudi population from 2017 to 2021. The population for this study includes new cases visiting hospitals for routine health check-ups or related to various medical conditions, as well as individuals visiting screening camps outside hospitals in remote areas and schools. Patient data, specifically [25(OH)D] concentration measured through blood samples, were assessed by ROCH COBAS e-411 analyzers. The findings revealed a period prevalence of 67.3% (n = 15,025) for [25(OH)D] deficiency (<30 ng/mL). This included n = 6,274 (28.1%) with insufficient (20–29 ng/mL), n = 8,014 (35.9%) with deficient concentration (<20 to 7 ng/mL), and n = 737 (3.3%) with severe (<7 ng/mL) [25(OH)D] concentration. Females were predominantly affected, n = 10,442 (69.5%), compared to males, n = 4,583 (30.5%). The most affected age group was 10–19 years old, with a mean concentration of [25(OH)D] as low as 21.1 ± 11.9 ng/mL. Trend analysis revealed a significant decrease in vitamin D deficiency prevalence from 32% to 9% between 2017 and 2020, with a slight increase to 18% in 2021. The findings of this study necessitate interventions based on age-specific patterns, providing crucial insights for targeted public health strategies aimed at enhancing vitamin D status in the Saudi population, particularly among the most affected groups such as females and younger individuals within the 10-19-year age group.